Complete discrimination of six individuals based on high-resolution melting of hypervariable regions I and II of the mitochondrial genome. (August 2009) - Gidlöf, Olof; Burvall, Sofia; Edvinsson, Lars; Montelius, Maria; Allen, Marie; Molin, Magnus
Analysis of mitochondrial DNA in forensic samples is routinely carried out by direct sequencing of hypervariable regions within the non-coding displacement loop. Although the accuracy and sensitivity of this method cannot be questioned, it is both time-consuming and labor intensive. Finding a way to rapidly pre-screen forensic samples—prior to sequencing, to reduce the number of samples that need to be sequenced—would greatly benefit forensic laboratories. Herein, we describe an assay for discrimination of DNA from different individuals based on high-resolution melting analysis of the two hypervariable regions HVI and HVII of the mitochondrial genome. By clearly distinguishing the DNA melting curves of six different individuals, we show that this assay has the potential to function as a rapid and inexpensive pre-screening method for forensic samples prior to DNA sequencing.